PRM-LIVE with Trapped Ion Mobility Spectrometry and Its Application in Selectivity Profiling of Kinase Inhibitors - Zhu, He; Ficarro, Scott B; Alexander, William M; Fleming, Laura E; Adelmant, Guillaume; Zhang, Tinghu; Willetts, Matthew; Decker, Jens; Brehmer, Sven; Krause, Michael; East, Michael P; Gray, Nathanael S; et al. (Analytical chemistry, 2021)
Parallel reaction monitoring (PRM) has emerged as a popular approach for targeted protein quantification. With high ion utilization efficiency and first-in-class acquisition speed, the timsTOF Pro provides a powerful platform for PRM analysis. However, sporadic chromatographic drift in peptide retention time represents a fundamental limitation for the reproducible multiplexing of targets across PRM acquisitions. Here, we present PRM-LIVE, an extensible, Python-based acquisition engine for the timsTOF Pro, which dynamically adjusts detection windows for reproducible target scheduling. In this initial implementation, we used iRT peptides as retention time standards and demonstrated reproducible detection and quantification of 1857 tryptic peptides from the cell lysate in a 60 min PRM-LIVE acquisition. As an application in functional proteomics, we use PRM-LIVE in an activity-based protein profiling platform to assess binding selectivity of small-molecule inhibitors against 220 endogenous human kinases.
Keywords: Mass Spectrometry; hmotnostní spektrometrie; Proteomics; lidé; peptidy; proteiny; proteomika; Peptides; Ion Mobility Spectrometry; iontová mobilní spektrometrie; Proteins; Humans